Signal Biases Calibration for Precise Orbit Determination of the Chinese Area Positioning System using SLR and C-Band Transfer Ranging Observations. (19th April 2016) - Fen, Cao; Xuhai, Yang; Zhigang, Li; Liang, Chen; Chugang, Feng
Abstract : In C-Band transfer measuring systems, the Precise Orbit Determination (POD) precision of Geostationary Earth Orbit (GEO) satellites is limited by signal biases such as the station delay biases, transponder delay biases, the ionospheric delay model bias, etc. In order to improve the POD precision, the signal biases of the Chinese Area Positioning System (CAPS) are calibrated using Satellite Laser Ranging (SLR) and C-Band Transfer Ranging (CBTR) observations. Since the Changchun SLR site and C-Band station are close to each other, the signal biases of the Changchun C-Band station are calibrated using the co-location comparison method. Then the signal biases of the other two CAPS C-Band stations, located in Linton and Kashi, are calibrated using the combined POD method, with the signal biases of the Changchun C-Band station being fixed. After the signal biases are calibrated, the RMS of the line-of-sight residuals of the Changchun SLR observations decrease by 0·4 m, with the percentage improvement being 75·19%.